The Exclusive Nature - Olsen, Torjer A. (Journal of religion in Europe, 2014)
In Sámi Christian educational texts, the Indigenous Sámi are presented as having a particularly close relation to nature. This is presented as a defining factor of both Sáminess and of Sámi Christianity. The article consists of the analysis of two educational texts, a catechism and a website, made/written by Sámi Christians. The close relation to nature is interpreted as part of global eco-indigenism, a tendency to combine the political movement of indigenism and the claim that indigenous peoples have a special kind of closeness to nature. In sum, what happens is a canonisation of Sámi Christian identity, excluding Sámi who are not living in close proximity to nature.